2017
DOI: 10.1158/1535-7163.mct-16-0499
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin-Induced Apoptosis in Osteosarcoma Cells: A Key Role of RhoA-AMPK/p38 MAPK Signaling in Antitumor Activity

Abstract: Osteosarcoma is the most common type of primary bone tumor, novel therapeutic agents for which are urgently needed. To identify such agents, we screened a panel of approved drugs with a mouse model of osteosarcoma. The screen identified simvastatin, which inhibited the proliferation and migration of osteosarcoma cells in vitro Simvastatin also induced apoptosis in osteosarcoma cells in a manner dependent on inhibition of the mevalonate biosynthetic pathway. It also disrupted the function of the small GTPase Rh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 40 publications
6
73
0
Order By: Relevance
“…To identify effective therapeutic drugs for osteosarcoma, we screened 1164 US Food and Drug Administration (FDA)–approved compounds all at the same concentration (1.92 μM), using a novel humanoid robot (Robotic Biology Institute, Tokyo, Japan) . Calcitriol decreased the viability of AXT cells by 44% of the control level (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify effective therapeutic drugs for osteosarcoma, we screened 1164 US Food and Drug Administration (FDA)–approved compounds all at the same concentration (1.92 μM), using a novel humanoid robot (Robotic Biology Institute, Tokyo, Japan) . Calcitriol decreased the viability of AXT cells by 44% of the control level (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, we generated a mouse model of osteosarcoma by overexpressing c‐MYC in bone marrow stromal cells derived from Ink4a/Arf knockout mice . Inoculation of these cells, designated AXT cells, into syngeneic C57BL/6 mice results in rapid formation of lethal tumors with metastatic lesions that faithfully mimic human osteoblastic osteosarcoma, providing a useful model for preclinical studies …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Simvastatin is therefore partially effective by inducing oxidative stress. Similar to the triggring effect of simvastatin on apoptosis of osteosarcoma cells [135], the stimulation of eryptosis by simvastatin on cell membrane scrambling requires apparently activity of p38 kinase, which is known to participate in the orchestration of eryptosis [53]. Accordingly, the effect of simvastatin on annexin-V-binding is significantly blunted in the presence of p38 kinase inhibitor SB203580.…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer effects of statins have been reported in a variety of cancer types including osteosarcoma [29][30][31]. Although RhoAmediated signaling has been shown to be involved in simvastatin-induced apoptosis and atorvastatin-reduced invasion of osteosarcoma cells [17,32], Olivia et al identified CYR61 as a new target of atorvastatin that was independent from RhoA signaling [13]. CYR61 has been reported to be an oncogene and is associated with osteosarcoma aggressiveness and metastatic potential [11].…”
Section: Discussionmentioning
confidence: 99%